The future of Eastern Europeans in Post-Brexit United Kingdom - Jessica Reed (European Institute of Romania, 2018)
The United Kingdom's relationship with the European Community has been a rather strained and inconsistent one ever since the latter's initial conception and birth against the backdrop of the World War II. Nevertheless, starting out as risky political bet by former Prime Minister David Cameron, very few actually expected the EU referendum in Britain to end as it did, the vote to leave with 52% versus 48% sending shockwaves throughout Europe and the whole world. In the immediate aftermath, the value of the pound plummeted, Scottish politicians once again raised the prospect of Scottish independence from the UK and discussions about the "Good Friday Agreement" re-emerged, threatening to break up the nation, and deep fractures in British society were brought to the surface of political and social commentary. At the moment of writing, there are approximately six months to go until the official withdrawal date - set on 29th March 2019, and the prospects of 'no deal Brexit' are looming large. The purpose of this working paper is to highlight British attitudes to immigration and critically assess the situation facing a group of so-called "migrants" that was heavily implicated throughout the EU referendum: Eastern Europeans, in particular Polish and Romanian citizens residing and working in the UK. The paper will examine EU mobility in the UK and how the issue has featured in media and political discourse. Then, it will discuss how immigration featured in the campaign to leave the European Union and the impact of Brexit on hate crime in the UK, before moving on to shed some light on how Eastern Europeans are and are not being protected in Brexit discussions.
Keywords: 330; United Kingdom; European Union; Eastern Europe; migration; Brexit